The Effect of Virgin Coconut Oil (VCO) in Healing and Preventing Pressure Ulcers in Immobilization Patients: A Literature Review - Gusti Pandi Liputo; Ibrahim Suleman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pressure ulcers or bedsores are a serious problem in patients experiencing long-term immobilization or bed rest. This condition is caused by prolonged pressure on specific body areas, leading to tissue damage and potentially increasing the duration of patient care. Virgin Coconut Oil (VCO) is known to contain lauric acid, antioxidants, and vitamin E, which can help maintain skin moisture, increase elasticity, and prevent irritation and infection. Some studies show that VCO, especially when applied with effleurage massage techniques, has the potential for the prevention and healing of pressure ulcers. Objective: This study aims to review the effectiveness of using VCO as a preventive and therapeutic agent for patients at high risk of pressure ulcers. Method: This study is a literature review of several studies published between 2020 and 2024. Research results related to the application of VCO in immobilized patients were analyzed, focusing on its effects on pressure ulcer risk, Braden score, and tissue healing improvement.Results: The literature review identified eight studies for inclusion in the final analysis. All articles used quasi-experiments. he application of VCO significantly increased the Braden scores of patients receiving care. Effleurage massage with VCO effectively reduced the risk of pressure ulcers and accelerated granulation tissue formation in grade I and II wounds. Additionally, comparisons between VCO and virgin olive oil showed that VCO was superior in reducing the risk of pressure ulcers in ICU patients.Kesimpulan: Virgin Coconut Oil (VCO) has been proven effective as a natural intervention for the prevention and healing of pressure ulcers in patients with limited mobility. The use of VCO in nursing practice can improve patients’ quality of life, reduce the risk of skin complications, and shorten the duration of care. Further research is recommended to explore the use of VCO with additional methods and technology to maximize its benefits in pressure ulcer care.